ANALYSIS OF THE LEGAL AMBIGUITY OF JUDGES' ETHICS VIOLATIONS IN PERMANENT CRIMINAL VERDICT - Amalia, Nazwa; Almi, Ara Annisa; Zaki, Aulia (Sriwijaya Crimen and Legal Studies, 2024)
The judge's verdict in the judicial system in a legal country has an important meaning in realizing justice and public order. The judge, in carrying out his obligation to decide a criminal case, besides guided by Indonesian Code of Criminal Procedure (KUHAP) and the Indonesian Criminal Code (KUHP) rules, must also be guided by the Code of Ethics and Code of Conduct for Judges (KE and PPH). This article analyzes legal certainty regarding criminal verdicts from judges proven to have violated the code of ethics. This research method uses normative Judicial legal research. The research results show that in recent times, there has been a lot of public news regarding alleged KE and PPH violations. Some of this resulted in verdicts against several judges the Judicial Commission sanctioned. This report also found several reports of alleged violations of the Judge's Code of Ethics related to criminal cases. Apart from that, conditions were also found where the judge's code of ethics was questioned because the judge violated the judge's duties and authority, namely accepting, examining, and deciding criminal cases based on the principles of freedom, honesty, and impartiality in court. The suggestion put forward is the need for regulation in the Criminal Procedure Code regarding the issue of whether a criminal verdict is valid or not if a judge is proven to have violated the code of ethics.